Symposium 2: ‘Employability’ and the digital future of work - Beetham, Helen (Proceedings of the International Conference on Networked Learning, 2016)
This paper discusses the role of networked technologies in education through the lens of work, both the work carried out by academic and professional staff – refigured by the demands of digital institutions – and the 'employability' of graduates and college leavers that stands over their educational experience as its supposed rationale, justification and destination. The paper draws on a recent literature review and interviews with staff in UK tertiary education to elucidate the changing nature of academic work and the demands for digital capability and engagement placed on education professionals. It goes on to explore academic work as exemplary of large-scale shifts not only in the kinds of work people do but in the way work is valued, engaged in, and managed in the lifecourse. It concludes by arguing that employability needs to be opened up within the curriculum as a series of critical explorations rather than deployed as received knowledge about the kinds of learning outcome that are desirable. In the spirit of radical pedagogy, it suggests that academics support these explorations when they engage critically with the circumstances of their own digital labour.